Effect of Using Recycled Coarse Aggregate to the Bond Stress in Term of Beam Splice Specimens - Abbas Sadiq Mohammed; Ali Laftah Abbas (Civil Engineering Journal, 2019)
In fact, demolition west disposal represents a serious problem in the civil engineering work since such materials are accumulated in large quantities. In this way, using these materials in new construction is considered a good sustainable and cost effective solution. The basic objective of this study is to investigate the behavior of lap splice when recycled coarse aggregate is used in structural members by experimental program. This program comprises casting 12 beam splice specimens. Two mix designs are proposed with nominal compressive strength of 20 and 30 MPa, more precisely, the degrees of coarse recycled aggregate partial replacement ratio that taken throughout this study are 0, 50 and 100% respectively using a crushed concrete casted with the same original mixes defined.  Since a considerable lack of information was observed about the role of recycled coarse aggregate when the bond stress is taken into account, the beam splice specimens during this study were devoted to investigate lap splice bond strength in both singly and doubly beams to discover the desired behavior in tension and compression. The results showed that the degree of recycled coarse aggregate decreases the consequent bond stress in term of beam splice specimens for singly and doubly beams. The brittle failure behavior is evident in the entire beam specimens that conducted throughout this study.